Physical literacy conceptions in teacher training: a longitudinal study - Hernaiz-Sánchez, Ariadna; González-Valeiro, Miguel A.; Romero-Chouza, Óscar; Fernández-Villarino, María A. (Frontiers in Psychology, 2025)
IntroductionPhysical literacy (PL) embodies the motivation, confidence, physical competence, knowledge, and understanding necessary to sustain physical activity throughout life. Understanding how future physical education (PE) teachers conceptualize PL is essential for its effective implementation in schools. This longitudinal study examined the evolution of trainee teachers’ conceptions of PL across 5 years of initial teacher education in Spain.MethodsA total of 397 students (76% male; 22.6 ± 3.8 years) from two universities participated, with data collected at three time points: the first and final years of the bachelor’s degree in Physical Activity and Sport Sciences and the final year of the master’s degree in Teacher Training. Responses to the open question “What is a physically literate student?” were coded into 13 conceptual categories and analysed through two-step cluster analysis, multinomial logistic regression, and chi-square tests (p < 0.05).ResultsThree profiles emerged: (1) an Enjoyment-Oriented group focused on participation and enjoyment in physical activity; (2) a Performance-Centred group emphasizing motor skills, physical fitness, and sport competence; and (3) a Competence-Driven group highlighting motor competence and active lifestyles. Over time, students’ conceptions shifted significantly (χ2 = …, p < 0.05) from enjoyment and personal competence towards motor competence and performance-related attributes, with lifestyle habits and maternal education predicting cluster membership.DiscussionThese findings indicate that initial teacher education may foster more performance-oriented understandings of PL, underscoring the need for balanced curricula that integrate physical, cognitive, and affective dimensions of physical literacy.